The Implementasi Sistem Informasi Akuntansi Terhadap Kinerja Keuangan Perusahaan Manufaktur di Indonesia - Ihsanuddin, Mokhammad; Supriyanto, Supriyanto; Oktriyani, Oktriyani; Akhrima, Nina; Nazila, Nur Alvisyahri; Fauzia, Alysya; Nurlaila, Lala; Nurmuhammad, Riezky Zulfikar; Hadida, Vanya Shaquila; Sugiharto, Sugiharto (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This research evaluates the effect of the implementation of an Accounting Information System (AIS) on the financial performance of manufacturing companies in Indonesia using secondary data from the annual financial reports of companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period. Through multivariate analysis using SPSS version 25, the research results show that SIA implementation significantly influences financial performance, with the largest positive impact on Return on Equity (ROE). SIA contributes to increasing Return on Assets (ROA), Return on Equity (ROE), and profitability (PROF), indicating that SIA can increase the efficiency of asset use, equity profitability, and the company's profit ability. These findings provide important insights for manufacturing companies in utilizing information technology to improve their financial performance, as well as aligning with existing literature on the role of AIS in financial management.